Alternative outlines of immigration: A case of repopulation of existing abandoned Spanish towns. Issue 1 (2nd January 2016) - González-Torres, Rolando
Abstract: One of the most sensitive tragic situations today, in regards to human relations in Europe is the illegal immigrants' issue. But it is no longer mainly a subject of borders' transgression, obsolete sovereignties, or labor-hand marketing. Huge population masses without fixed course are driven by different urgent motives from their countries of origin – North Africa, sub-Saharan Africa, Middle East, Eastern Europe, – they have no choice but to move in search of places to settle and provide a decent home for their families. In the form of another drama in this case of heritage and environment, some old rural villages of Spain – as there are in other southern European countries – have been completely abandoned and their current status, in ruins, results of the economic, political and urban trends of the past 75 years. Connecting these issues, it could be considered a promising future for those homeless families as well as for those dying towns through integrated solutions of mutual benefit. This research examines the resurgence of human being's value over any other concept of relative temporarily value, and where a town's roots are more important than any commercial interest and real estate speculation.